West Jakarta Government’s Paradiplomacy towards Global Public in Kalideres Refugee Issues - Hubert, Ignatius; Dermawan, Windy (Society, 2020)
This research analyzes international refugees’ presence in Indonesia, which gives local challenges for the Indonesian subnational Government as a transit location. This research uses a paradiplomacy perspective to analyze the West Jakarta Government’s response to the foreign refugees in its territory. West Jakarta is one of the Administrative Cities in the Special Capital Region of Jakarta. This research uses a qualitative research method. The research data sources were collected and analyzed from literature studies, current news, and socio-political theories. This research found that West Jakarta Government’s paradiplomacy occurs due to differences in regulations applies. Moreover, this process can be parallel alongside the Central Government (Indonesian Government) in handling refugees in their territory following a local-regional wisdom approach. The West Jakarta Government’s paradiplomacy carried out by coordinating the distribution of aid to refugees, working with stakeholders in handling international and national refugee issues, and managing refugee handling policies in transit locations where refugees live, especially in Kalideres, West Jakarta, Indonesia. These handling efforts aim to prevent horizontal conflicts between refugees and local people and achieve subnational interests in the form of support materially, financially, and politically.